Nos « silences construits » : nommer la violence épistémique au fondement de la théorie queer - Camille Back (Genre, Sexualité et Société)
On the occasion of the release of the French translation of Borderlands, this article aims to look back at how Gloria Anzaldúa’s contributions have been systematically silenced during the emergence of queer theory. Drawing on queer of color critique, it highlights the fact that queer theory is based on the erasure or marginalization of the inputs of many writers of color. After exposing the epistemic violence of its “founding” texts, I will reinvest the metaphor of the “black hole” suggested by Evelynn Hammonds in “Black (W)holes and the Geometry of Black Female Sexuality” (1994) in order to take into consideration not only our “constructed silences”, but also our blank spots. Finally, I will focus on how the French translation policy and the adoption of the “waves” metaphor in order to describe the development of queer theory has contributed to renewing these practices of marginalization and erasure, while reproducing blank spots in the analysis.